2020
DOI: 10.1080/20442041.2020.1711681
|View full text |Cite
|
Sign up to set email alerts
|

Toward predicting climate change effects on lakes: a comparison of 1656 shallow lakes from Florida and Denmark reveals substantial differences in nutrient dynamics, metabolism, trophic structure, and top-down control

Abstract: Rapid climate changes may potentially have strong impacts on the ecosystem structure and nutrient dynamics of lakes as well as implications for water quality. We used a space-for-time approach to elucidate such possible effects by comparing data from 1656 shallow lakes (mean depth <3 m) in north temperate Denmark (DK) and subtropical Florida (FL). The lakes were categorized into 7 total phosphorus (TP) classes within the range of 2 to 300 µg L −1. Physicochemical variables showed significant seasonal differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 59 publications
(73 reference statements)
3
27
0
Order By: Relevance
“…We found that species richness was significantly linearly related to lake productivity (expressed as Chla), which is in accordance with several studies from the temperate climate zone [7,39,40]. The relationship between species richness and environmental factors has been well studied in Europe [3,7,10,16,41,42]. Our results differ from those of [3], which showed a unimodal relationship with TP, and those of Helminen et al (2000) [43], which revealed a reduction in species number in eutrophic Finnish lakes that was attributed to oxygen deficiency.…”
Section: Discussionsupporting
confidence: 90%
“…We found that species richness was significantly linearly related to lake productivity (expressed as Chla), which is in accordance with several studies from the temperate climate zone [7,39,40]. The relationship between species richness and environmental factors has been well studied in Europe [3,7,10,16,41,42]. Our results differ from those of [3], which showed a unimodal relationship with TP, and those of Helminen et al (2000) [43], which revealed a reduction in species number in eutrophic Finnish lakes that was attributed to oxygen deficiency.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies on freshwater invertebrates across large spatial scales suggest that, in addition to spatial factors, climatic gradients (e.g., temperature, precipitation) and ecosystem size are dominant predictors of species richness, community composition and average organismal size in lakes (Hayden et al., 2019; Meerhoff et al, 2012). Studies on processes of community assembly for fishes in freshwater lakes likewise identified dominant roles of abiotic filtering at large spatial scales (Brucet et al., 2013; Emmrich et al., 2014; Jeppesen et al., 2020). Fish population densities and population size structure are modified primarily by productivity of the ecosystems (Arranz et al., 2016; Brucet et al., 2013), and dispersal limitation of small fish species can affect local fish species occurrences (Mehner et al., 2014; Olden et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…He frequently told us that 'this Florida-Denmark comparison is really good stuff for understanding climate change effects on lakes-get it published!' It took a while, but now it is done (Jeppesen et al 2020), and we are very happy to be able to publish it in a special issue celebrating his legacy." Meryem Beklioğlu wrote: "As a young MSc graduate awarded a PhD scholarship from the Turkish government, I was searching for a supervisor to carry out my PhD on freshwater ecology but had no background and no idea who to study with.…”
Section: Brian Moss: the Wizard Of Shallow Lakesmentioning
confidence: 99%